The Meaning of Life: Belief and Reason in the Abortion Debate - Borgmann, Caitlin E. (Columbia Journal of Gender and Law, 2009)
In 1993, a man named Michael Griffin killed David Gunn, a forty- seven-year-old doctor who provided abortions at a clinic in Pensacola, Florida. Before shooting Gunn three times in the back, Griffin yelled, “Don’t kill any more babies!” According to news reports, protestors present at the clinic that day, members of a “militant” anti-abortion-rights group, were elated, shouting, “Praise God! Praise God! One of the baby- killers is dead.”, Yet “mainstream” anti-abortion-rights groups, who are more representative of the majority of abortion-rights opponents, were quick to renounce the murder, sensing “a public-relations disaster.” In August 2008, then-presidential nominees Senators Barack Obama and John McCain appeared separately at a religious forum hosted by best-selling author and evangelical pastor, Rick Warren. Warren asked each candidate at what point “a baby [is] entitled to human rights.”, McCain responded simply, “At conception.” This position appears consistent with Griffin’s view that abortion amounts to killing babies, and at odds with McCain’s own support for stem cell research and for abortion under limited circumstances. Yet, far from challenging McCain, Warren seemed satisfied that McCain’s answer encapsulated a complete and coherent moral position on abortion. Suggesting that no further examination was warranted, he remarked, “Okay. We don’t have to go longer on that one.” For his part, Obama answered that “if you believe that life begins at conception, then- and you are consistent in that belief-then I can’t argue with you on that.” Obama’s response mirrored the standard liberal position, which divorces the moral question of “life”-what it means and when it begins-from the legal questions of abortion and personhood.